Impacts of atmospheric ultrafast Kelvin waves on radio scintillations in the equatorial ionosphere. Issue 2 (25th February 2013) - Liu, Guiping; Immel, Thomas J.; England, Scott L.; Frey, Harald U.; Mende, Stephen B.; Kumar, Karanam K.; Ramkumar, Geetha
Abstract : [1] We present a statistical analysis of the amplitudes of GPS scintillations (S4 index) observed throughout 2008–2010 using the satellite radio occultation measurements of the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC). Here, for the first time, periodic variability in the occurrence of S4 is investigated using these data. Significant variations of S4 with periods of 2.5–4 days (quasi‐3 days) are identified from the observations during postsunset hours (1900–2400 local time) between 15°S– 15°N magnetic latitude during this 3 year interval. Coherence analyses of these variations with the geomagnetic Ap index, solar EUV irradiance, and atmospheric wind measurements from an equatorial mesosphere meteor radar at Thumba, India ( 8.5°N, 77°E) are performed, providing a measure of the relationship between variations in the scintillations and potential drivers. The quasi‐3 day variations in S4 are found to covary with the variations of the three drivers examined. In particular, the S4 signatures are found to be coherent with the atmospheric ultrafast Kelvin (UFK) planetary waves characterized by the zonal wind measurements of the radar. This study shows that these UFK waves are as important as the solar and geomagnetic drivers in forcing the day‐to‐day variations of the occurrence of equatorial spread F . Key Points: For the first time COSMIC S4 data are used to study scintillation periodicity. A stringent examination of S4 quasi-3 day variation and atmospheric UFK waves. Large‐scale day‐to‐day variations of equatorial ionospheric scintillations.